A retrospective study on the epidemiological and clinical characteristics of SARS-CoV-2 infection among the affected pediatric population attending a tertiary care hospital in Eastern India - Biswas, Tanusri; Chaudhury, Nabamita; Mondal, Raston; Chatterjee, Aroni; Chattopadhyay, Saswati (Asian Journal of Medical Sciences, 2022)
Background: Novel coronavirus infections cause major morbidity and mortality globally in the all age groups, including the pediatric population. Viral respiratory infections in children may act as a source of infection especially those with asymptomatic SARS-CoV-2 infections. Aims and Objectives: The aim is to analyze the SARS-CoV-2 characteristics in pediatric age group. Materials and Methods: Ninety seven children neonate to 5 years age tested positive by RT-PCR were included in the study. Detailed data on socio-demography, epidemiology, clinical characteristics, laboratory findings, comorbidities, management, and outcome of the study population were collected. Results: Sex distribution showed 47 (48.4%) male and 50 (51.5%) female. Among these 97, 5 children (5.1%) were <28 days of age, 30 children were (31%) neonate to infant age, and 62 children were (63.9%) above 1 year but <5 years of age. The group was divided into two—one with 56 children (57.7%) who were discharged, 2nd with 41 (42.3%) hospitalized children. 1st group was asymptomatic (64.3%)/mildly symptomatic (35.7%). In 2nd group 36.5% were moderately symptomatic, 29.2% were with severe complications, and 34.3% of children were critical–22 (52.6%) required PICU admission–17 children (41.4%) required mechanical ventilation and 36 (87.8%) required respiratory support. Conclusion: Reports state that COVID-19 infection is mild in the pediatric population but our findings suggest that some children can develop severe/critical infection requiring hospitalization, respiratory support, and mechanical ventilation.